EprX associates with concurrent shifts in antimicrobial resistance and virulence in clinical bloodstream E. coli: a putative adaptive node for bacterial fitness - Afeng Wang; Yingying Guo; Jichao Zhu; Yuliang Sun; Zhaochen Huang; Tinliang Lin; Chen Liang; Cunnan Xu; Xinhua Qiang; Jie He; Hongchang Zhou; Longwen Shu; et al. (Frontiers in Cellular and Infection Microbiology, 2026)
Bloodstream infections (BSIs) caused by E. coli represent a growing global threat, driven by escalating antimicrobial resistance (AMR) and sustained virulence. However, the regulatory mechanisms linking these two phenotypes remain poorly understood. Here, we identify EprX , a previously uncharacterized YjbI-type pentapeptide repeat protein (PRP), a locus that our data suggest may influence metabolic and transcriptional profiles in clinical BSI E. coli isolates. Genomic screening of 85 clinical BSI strains reveals that eprX is present in 21.2% of isolates, often within distinct genomic contexts suggestive of mobile acquisition. Using λ-Red recombineering, we constructed eprX knockout mutants. Loss of eprX is associated with altered antimicrobial resistance profiles, increasing susceptibility to gentamicin, ciprofloxacin, and levofloxacin. This phenotype is consistent with upregulation of outer membrane porin genes ( ompC , ompF ) and downregulation of multidrug efflux pump genes ( macB , mdtC , emrB ) and two-component regulatory system genes. eprX deficiency also appears to correlate with attenuated virulence in our assays, as evidenced by improved survival of Galleria mellonella larvae (65–95% at 72 h post-infection vs. 40–60% for wild-type strains) and reduced adhesion to and invasion of human HeLa cells. Transcriptomic profiling reveals that eprX carriage is associated with broad, coordinated shifts in the expression of genes involved in LPS transport ( lptG / lptF ), type ;II secretion system components ( gspD / gspE / gspF ), autotransporter adhesins ( ag43 ), and flagellar assembly, suggesting potential disruptions in outer-membrane integrity, biofilm formation, and virulence programs. Our data suggests that eprX is a genetic locus whose presence correlates with concurrent shifts in resistance maintenance and virulence traits, representing a putative adaptive node within the E. coli fitness landscape.